Self-winding liquid crystal elastomer fiber actuators with high degree of freedom and tunable actuation. (June 2022) - Hu, Zhiming; Li, Yunlong; Zhao, Tonghui; Lv, Jiu-an
Highlights: Bioinspired twistless strategy enables production of high-degree-of-freedom actuators. Diverse deformation modes integrated into a single fiber actuator. Fiber actuators allow both large length change and powerful actuation stress. Scalable manufacture of artificial muscle of liquid crystal elastomers. Abstract: Liquid-crystal-elastomer (LCE) fiber actuators capable of reversible, large-scale, programmable deformation in response to external stimuli have great potential in many applications, including artificial muscles, robotics, and wearable devices. Despite their exciting prospects, limitations -such as few modes of shape transformation in a single actuator due to limited degree of freedom (DOF), difficulty to concurrently gain large length change and powerful stress, lack of scalable manufacturing method - seriously restrict their engineering applicability. Here we present bioinspired self-winding LCE fiber actuators that possess diverse controllable shape transformations (bending, twisting, coiling, and shortening), a combination of high contraction ratio (1750%) and high stress (∼3.4 MPa), long term photomechanical robustness (over 1000 photodeformation cycles without obvious fatigue), and readily, scalable manufacture. Our fiber actuators can simultaneously conduct two or three kinds of deformation and thus enables complex morphing behaviors to manipulate objects (grabbing, dragging, lifting, and winding), and even drive gear set. We envision that these self-winding fiber actuators combined with high DOF, tunable actuation, photomechanical robustness, and mass production could be developed as high-performance artificial muscles for broad engineering applications.